HUBUNGAN ANTARA MENONTON IKLAN LINE WEBTOON DI TELEVISI TERHADAP MINAT MEMBACA KOMIK SECARA ONLINE PADA MASYARAKAT KOTA DENPASAR - Dani Febriyanti, Cinthya Nurrahmat; Pradipta, Ade Devia; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
From commercials that aired on television, Line Webtoon became one of the digital comics that advertise their products with the aim of people watching their ads can download online comic apps and increase reading interest in comics. The purpose of this research is to find out the relationship between watching Line Webtoon ads on television to the interest in reading comics online in the people of Denpasar. This research uses a type of associative with quantitative approach. Sampling techniques used are nonprobability sample techniques and purposive sampling methods. Analysis techniques used in research through several stages, namely research instrument test, classical assumption test, Multiple Linear Regression Analysis, Goodness of Fit Test and T Statistical Test and Determination Coefficient. The result of this study is watching Webtoon Line Ads on Television is able to influence the Interest in Reading Comics online in the people of Denpasar. Keywords: Line Webtoon Advertisement, Denpasar Citizens, Reading Interests, Digital Comics